2012
DOI: 10.2345/0899-8205-46.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Medical Device SALs And Surgical Site Infections: A Mathematical Model

Abstract: It is commonly accepted that terminally sterilized healthcare products are rarely the source of a hospital-acquired infection (HAI). The vast majority of HAIs arise from human-borne contamination from the workforce, the clinical environment, less-than-aseptic handling techniques, and the patients themselves. Nonetheless, the requirement for a maximal sterility assurance level (SAL) of a terminally sterilized product has remained at 10(-6), which is the probability of one in one million that a single viable mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Therefore, even if the SAL of the sterilized product is slightly different than a claimed SAL of 10 -6 , the SAL might be only something such as 10 -5.8 , a probability of a viable microorganisms of about one in six hundred fifty thousand, which is certainly not a level that can be called nonsterile as far as patient safety is concerned. 4 In ANSI/AAMI ST67, there are SALs other than 10 -6 that are recognized as "sterile," such as 10 -3 , 10 -4 and 10 -5 , which are acceptable based on certain criteria. 5 Because of this, the issue is not whether the fully processed product is sterile-it is sterile as far as patient safety is concerned.…”
Section: Featurementioning
confidence: 99%
“…Therefore, even if the SAL of the sterilized product is slightly different than a claimed SAL of 10 -6 , the SAL might be only something such as 10 -5.8 , a probability of a viable microorganisms of about one in six hundred fifty thousand, which is certainly not a level that can be called nonsterile as far as patient safety is concerned. 4 In ANSI/AAMI ST67, there are SALs other than 10 -6 that are recognized as "sterile," such as 10 -3 , 10 -4 and 10 -5 , which are acceptable based on certain criteria. 5 Because of this, the issue is not whether the fully processed product is sterile-it is sterile as far as patient safety is concerned.…”
Section: Featurementioning
confidence: 99%
“…In another study using a mathematical model to evaluate the relationship of SAL to infection, it was demonstrated that there was no difference in the rate of infection when comparing ADM with an SAL of 10 −3 and 10 −6 . 34…”
Section: Understanding Adm Sterilitymentioning
confidence: 99%
“…In recent times, the incidence of infertility has progressively increased due to potential factors such as life stressors and delayed child-bearing age [1]. The development of assisted reproductive technologies has dramatically improved the outcomes of in vitro fertilization/embryo transfer (IVF/ET) in recent years.…”
Section: Introductionmentioning
confidence: 99%